Do Competitive Contexts Affect Mindreading Performance? - Colle, Livia; Dimaggio, Giancarlo; Carcione, Antonino; Nicolò, Giuseppe; Semerari, Antonio; Chiavarino, Claudia (Frontiers in Psychology, 2020)
Mindreading is contingent upon interpersonal context. Little is known about how competitive contexts influence mindreading skills. The idea was that the capacity to think about mental states would decline when individuals experiencing failure in competition. This study aims to assess effects of a competitive experience (a computer competitive PC game) on a sample of healthy subjects (119 participants). The sample was divided into two sub-samples. The experimental group underwent an experience of failure, consisting in a PC game of logic against a hypothetical opponent. The control group was required instead only to discuss past personal experiences of competitive interactions. The Metacognitive Assessment Interview was administered to each sub-sample for evaluating mindreading capacities. Self-report tests were additionally provided for evaluation of trait-based dispositions: self-esteem, perfectionism, narcissism. Results supported our hypothesis: induction of sense of failure compromises ability to describe one’s own mental states and mental states of others. This effect was more pronounced in the domain of self-reflection. Results remained significant after controlling for self-esteem, perfectionism, and narcissism. We discuss possible clinical implications of these findings and the importance of evaluating mindreading capacities under the pressure of social rank as well as of other social motive.